(untitled) (Cần Thơ, 2016)
Chapter 1: The Four Operations; Chapter 2: Large numbers and the Calculator; Chapter 3: Decimals ....
Keywords: Toán học,Mathematics; Dạy và học (Tiểu học),Study and teaching (Elementary)